Faktor Biotik dan Abiotik pada Tempat Perkembangbiakan Anopheles spp. di Desa Gunung Jati, Kecamatan Pagedongan, Banjarnegara, Provinsi Jawa Tengah - Dyah Widiastuti; Anggun Paramita Djati; Nova Pramestuti (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2017)
Malaria transmission in Gunung Jati Village, Banjarmegara needs serious attention because this village is malaria endemic area. This study aimed to investigate the biotic and abiotic environmental conditions at Anopheles spp. breeding sites in Gunung Jati village, Banjarnegara. Anopheles spp. larvae collection, measurement of abiotic factors and observation of microbiota on water samples were conducted on May 2015. Anopheles spp. larva was found in puddles on the banks of the river with larvae density was 5 larvae per dip. Water temperature conditions in all breeding sites ranged from 26-32 oC, the degree of acidity was neutral, with varying light intensity. Synedra are the most commonly found algae from all observed breeding sites. The environmental conditions were in accordance with the optimum conditions that support the development of Anopheles spp. larvae